Gen Z's Self-Disclosure Representation in Instagram Digital Interaction Bintang Emon - Tristan Fareliansyah Ega Naudy; Andika Sanjaya (Journal of Communication Studies, 2026)
The purpose of this study is to describe the form of self-disclosure carried out by generation Z through the comments column on Instagram content @bintangemon seen from the perspective of the Johari Window theory.This study uses a qualitative descriptive research type with a phenomenological approach based on communication netnography. Data analysis was conducted through thematic coding of questionnaire data and netnographic observation results. The results show that the Instagram comment column on the @bintangemon account has become a digital interaction space that allows Generation Z to conduct self-disclosure. Based on the analysis using the Johari Window theory, the forms of self-disclosure that emerged include the open area, namely the user's openness in relating content to personal experiences and feelings; the blind area, namely spontaneous comments that unconsciously show certain attitudes or emotions; the hidden area, namely the user's efforts to maintain privacy boundaries by not sharing all personal information, including through the use of a second account; and the unknown area, namely the emergence of new reflections and self-awareness through interactions with other users in the comment column. Thus, the Instagram comment column is not only a space for entertainment, but also a medium for self-expression and social reflection for Generation Z in the digital communication environment.